Causes of the premature birth of newborn babies hospitalized in Children’s’ Clinical Hospital in Lublin - Rudnicka-Drożak, Ewa; Rybojad, Beata (Polish Journal of Public Health, 2009)
Introduction. The period of intrauterine life is the first step in the individual growth, decisive for later development and health of human beings. During this period which is characterized by a very dynamic change, intense physical development is important to limit the impact of negative factors on the foetus. The increasing number of neonates born prematurely with low birth weight and developmental defects is the relevant issue to take tests to determine the relationship between the course of pregnancy and the influence of various environmental factors that influence the foetus during pregnancy. Aim. The aim of this study was to analyze the reasons of prematurity. Materials and methods. The survey included 104 mothers and their neonates hospitalized in The Department of Pathology of Neonates in Children’s’ Clinical Hospital in Lublin. The method of research was the analysis of medical records and a questionnaire survey. We assessed anthropometric parameters of prematurely born, their foetal age, sequence of pregnancy and Apgar points. Results. The majority of neonates (58.65%) were infants of mothers residing in rural areas from the first pregnancy and the first given birth. The reasons for early delivery in 85.58% were on mothers’ side, foetal age and number of Apgar’s scale points, obtained in first minute after birth, were closely related to each other and influenced the period for which the newborn was present in the ward. Our assessment proved that factors such as a maternal age, state of mothers’ health, education and economic situation affected the health of the neonate and influenced the occurrence of premature births. Conclusions. Most premature births occurred among women living in rural areas. Health state of mothers before and during pregnancy and taking medications are some of the causes of lower weight of premature babies. Newborn babies of mothers smoking cigarettes and exposed to the tobacco smoke in their surroundings have smaller birth body weight. Performed studies showed that it is necessary to instruct the girls and women within the conceptual period and pregnant women about the healthy lifestyle.